Bibliometric analysis of publication trends and research hotspots in vagus nerve stimulation: A 20-year panorama - Li, Rongrong; Hu, Hantong; Luo, Ning; Fang, Jianqiao (Frontiers in Neurology, 2022)
Background: As a promising neuromodulation technique, vagus nerve stimulation (VNS) has been utilized to treat diverse diseases and the number of VNS studies has grown prosperously. Nonetheless, publication trends and research hotspots in this field remain unknown. The aim of this study was to perform a bibliometric analysis to systematically identify publication trends and research hotspots in VNS research within a 20-year panorama. Methods: The Web of Science core collection (WOSCC) database was retrieved to screen eligible VNS-related publications from 2002-2021. The online analytic tool of the WoSCC was used to analyze various bibliometric parameters, such as the number of annual publications, the output of countries/regions, journals, total citations, citations per publication, and the Hirsch index. Bibliometrics (http://bibliometric.com/) and CiteSpace (Version 5.6.R3) were used to identify research trends and hotspots. Results: 7283 publications were included for analysis. The annual number of publications increased stably, but it increased significantly in recent years. The top 5 prolific counties were the United States, China, Germany, England, and France. The top 5 productive institutions were the University of California (Los Angeles), Harvard Medical School, Harvard University, University College London, and the University of Texas at Dallas. Notably, there was a geographical imbalance in countries and institutions. Besides, Epilepsy & Behavior, Epilepsia, and Plos One were the top 3 journals with the largest numbers of VNS publications. Michael P Kilgard was the most prolific author. Moreover, evolving research hotspots mainly included the effectiveness and mechanism of VNS on epilepsy, the role of VNS as an anti-inflammatory regulator, the application of VNS for psychiatric disorders, and the neuromodulation effect of VNS in headache management. Conclusion: This study has revealed the overall publication trends and evolving research trends at a global level over a 20-year panorama. The potential collaborators, institutions, hotspots, and future research trends are also identified in this field, which are helpful for guiding new research directions of VNS.